Deficits of Affect Mentalization in Patients with Drug Addiction: Theoretical and Clinical Aspects. (11th November 2013) - Savov, Svetoslav; Atanassov, Nikola
Abstract : Traditionally treated with wariness, drug addictions have provoked a serious interest in psychodynamically oriented clinicians in recent decades. This paper discusses the development of contemporary psychodynamic conceptualizations of addictions, focusing specifically on mentalization-based theories. The concept of mentalization refers to a complex form of self-regulation which includes attribution of psychological meaning to one's own behavior and affective states, as well as those of the others. We hypothesize that drug-addicted patients have severe impairments in mentalizing, associated with developmental deficits, characteristic for the borderline personality disorder and psychosomatic conditions. Psychodynamic models of mentalization and their corresponding research operationalizations are reviewed, and implications for a contemporary understanding of drug addictions and psychotherapy are drawn. The authors propose that mentalization-oriented theories provide an adequate conceptualization, which is open to empirical testing and has clear and pragmatic guidelines for treatment.